Role of In-Service Inspections in Nuclear Power Plants (NPPs) - Khan, M.; Awan, M.U.F.; Lal, K.; Gulab, M.; Ahmed, S.; Ahmed, Z. (The Nucleus, 2023)
The National Centre for Non-destructive Testing (NCNDT) since its inception in 1995 has been providing Pre-Service Inspections (PSI) and In-Service Inspections (ISI) services to the nuclear power plants (NPPs) in the country. In Pakistan, a total of six NPPs are operational with a cumulative capacity of 3620 MWe. All the efforts are made to ensure the safe and reliable operation of NPPs and the provision of an uninterrupted supply of electricity to improve the life of the common man. While extreme care is taken during the design, construction and commissioning of the structures, systems and components, a constant health monitoring system has to be ensured throughout the life (i.e., 40-50 years) of NPPs in accordance with the design parameters. The plant-specific codes & standards explain the ISI methods and acceptance criteria for critical life-limiting components, pressure boundary components and welds etc. Recently remotely controlled, advanced mechanized inspection systems for the inspection of reactor pressure vessels (RPV) and steam generators (SGs) have been procured. These systems are being used during the re-fueling outages (RFOs) of NPPs. Different conventional and non-conventional NDT methods were used for inspection. The components where unacceptable indications are revealed by ISI are repaired, replaced, or isolated. The baseline data generated during PSI is used for the comparison and surveillance. The observations made during ISI are subjected to thorough review and analysis by qualified experts to obtain assurance that unacceptable degradation in component quality is not occurring and it remains fit for service.